2021
DOI: 10.1002/gps.5507
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study into change of vitamin D levels, depression and frailty among depressed older persons

Abstract: Objectives While vitamin D is involved in frailty as well as depression, hardly any study has examined the course of vitamin D levels prospectively. The objective of this study is to examine whether a change of vitamin D in depressed older adults is associated with either depression course, course of frailty, or both. Methods The study population consisted of 232 of 378 older adults (60–93 years) with a DSM‐IV defined depressive disorder participating in the Netherlands Study of Depression in Older persons, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, low VitD levels are associated with an increased risk of morbidity and mortality at all levels of frailty (Jayanama et al, 2018), and higher levels were related to reduced risks of frailty progression (Swiecicka et al, 2017). The interaction between the course of frailty and change in VitD levels is presented in the study by Van Den Berg et al (2021), in which it was observed that an increase in VitD levels proved to be related to a decrease in continuous frailty score, that is, each frailty criterion less was related to a VitD increase of 3.04 nmol /L. In this context, oral VitD supplementation has been considered a promising approach to frailty and its consequences (Jayanama et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, low VitD levels are associated with an increased risk of morbidity and mortality at all levels of frailty (Jayanama et al, 2018), and higher levels were related to reduced risks of frailty progression (Swiecicka et al, 2017). The interaction between the course of frailty and change in VitD levels is presented in the study by Van Den Berg et al (2021), in which it was observed that an increase in VitD levels proved to be related to a decrease in continuous frailty score, that is, each frailty criterion less was related to a VitD increase of 3.04 nmol /L. In this context, oral VitD supplementation has been considered a promising approach to frailty and its consequences (Jayanama et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Three observational studies have been published since the most recent meta-analysis. 96 98 In these studies, the relationship between depression and VIT-D deficiency was less clear. One study failed to find a significant difference in participants with non-psychotic depression and controls.…”
Section: Vitamin D and Serious Mental Disordersmentioning
confidence: 97%
“… 97 Another study, following older adults with a depressive disorder over 2 years, found that an increase in VIT-D concentrations was significantly associated with improved frailty scores when adjusted for depression, but not independently with improvement of depression. 98 …”
Section: Vitamin D and Serious Mental Disordersmentioning
confidence: 99%